Unexpected distribution patterns of Carduiceps feather lice (Phthiraptera: Ischnocera: Philopteridae) on sandpipers (Aves: Charadriiformes: Scolopacidae). (2nd February 2017) - GUSTAFSSON, DANIEL R.; OLSSON, URBAN
Abstract: The louse genus Carduiceps Clay & Meinertzhagen, 1939 is widely distributed on sandpipers and stints (Calidrinae). The current taxonomy includes three species on the Calidrinae ( Carduiceps meinertzhageni, Carduiceps scalaris, Carduiceps zonarius ) and four species on noncalidrine hosts. We estimated a phylogeny of four of the seven species of Carduiceps (the three mentioned above and Carduiceps fulvofasciatus ) from 13 of the 29 hosts based on three mitochondrial loci, and evaluated the relative importance of flyway differentiation (same host species has different lice along different flyways) and flyway homogenization (different host species have the same lice along the same flyway). We found no evidence for either process. Instead, the present, morphology‐based, taxonomy of the genus corresponds exactly to the gene‐based phylogeny, with all four included species monophyletic. Carduiceps zonarius is found both to inhabit a wider range of hosts than wing lice of the genus Lunaceps occurring on the same group of birds, and to occur on Calidris sandpipers of all sizes, both of which are unexpected for a body louse. The previously proposed family Esthiopteridae is found to be monophyletic with good support. The concatenated dataset suggests that the pigeon louse genus Columbicola may be closely related to the auk and diver louse genus Craspedonirmus . These two genera share some morphological characters with Carduiceps, but no support was obtained for grouping these three genera together. Based on mitochondrial data alone, the relationships among genera within this proposed family cannot be properly assessed, but some previously suggested relationships within this proposed family are confirmed.